Iranian EFL teachers' reflective ability, their teaching experience, and learners' motivation: exploring possible relationships. Issue 1 (2nd January 2023) - Rezapour, Nesa; Fazilatfar, Ali Mohammad
ABSTRACT: Given the importance of reflection and experience in teaching and the undeniable role of motivation in learning, the present study aimed to investigate the relationships between teachers' reflective ability, their teaching experience, and learners' motivation. To this end, 50 English as a Foreign Language (EFL) teachers and 260 EFL learners participated in the study. Through quantitative phase, teachers completed a reflection questionnaire and learners completed both the Oxford Placement Test (OPT) and a motivation questionnaire. Correlational analysis and multiple regression indicated that there were significant positive relationships between teachers' reflective ability, their teaching experience and learners' motivation. Besides, the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach was used and it showed the positive significant relationships among the variables. Pedagogical implications and suggestions for further studies were presented based on the findings of the current research too.